คาร์บอกซีเมทิเลชันบนผ้าฝ้ายกอซด้วยวิธีการดูดซับและวิธีการอัดรีด-อบแห้ง-บ่ม - ณัฐณิชา เฮงประภากร (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The objective of this research was to modify cotton gauze by carboxymethylation by exhaustion and pad-dry-cure method by etherification with sodium hydroxide and monochloroacetic acid. Effect of three factors of monochloroacetic acid, sodium hydroxide and reaction time on the degree of substitution on modified cotton gauze were studied. Blood clotting, antibacterial, chitosan and silver nitrate absorption, water absorption, whiteness and bursting strength of the unmodified and modified cotton gauze were also studied. The results of this research found that increasing the concentration of monochloroacetic acid, concentration of sodium hydroxide and reaction time could provide a better relative degree of substitution on modified cotton gauze. Modified cotton gauze having a higher degree of substitution had a better absorption of chitosan and silver nitrate and retained two agents longer than those of unmodified cotton gauze and those of modified cotton gauze having a low degree of substitution. Modified cotton gauze had more efficiency of antibacterial than unmodified cotton gauze. Bursting strength of modified cotton gauze increased due to the shrinkage of cotton gauze. Whiteness and water absorption of modified cotton gauze were comparable to those of unmodified cotton gauze. Modified cotton gauze having the relative degree of substitution about 0.4-0.5 provided a faster rate of blood clotting, compared with cotton gauze having the higher relative degree of substitution.